A Gondwana pre-break up related magmatism in Bafoussam area, west Cameroon: source characteristics and 40Ar/39Ar geochronology - Djibril Kouankap Nono, Gus; Wotchoko, Pierre; Laure Tanko Njiosseu, Evine; Ganno, Sylvestre; Flore Tene Djoukam, Joelle; Seplong, Yannick; Guimolaire Nkouathio, David (International Journal of Advanced Geosciences, 2019)
The Gondwana pre-break up related formations in Bafoussam area are transitional calc-alkaline doleritic dykes exhibiting high Alumina and low Ti-Mg contents. Their REE compositions are similar to those of E-MORB (Nd/Nb≈1, Zr/Nb≤20). A high partial melting of about 20% of Garnet peridotites source having primitive mantle composition, is inferred to the studied rocks. They are slightly evolved 50<Mg#<54, and its clinopyroxenes are augite of high temperature (600°C-1100°C). The studied dykes were emplaced in a within-plate tectonic setting and yield a 40Ar-39Ar plateau ages of 229±7Ma. These ages are slightly different from those of dolerites from the Oban-Obudu massif (Nigeria), from the basaltic dyke of the Cameroon Volcanic Line and from the Karoo-Ferrar mafic magmatism, all interpreted as magmatism that preceded the break-up of Gondwana. The emplacement age of 229±7Ma of dolerites from Bafoussam area relates them to the very early stage of Gondwana pre-break up magmatism in central Africa.